2018
DOI: 10.3390/s18103543
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Cellular Dielectrophoretic Behavior Characterization Using Dielectrophoretic Tweezers-Based Force Spectroscopy inside a Microfluidic Device

Abstract: Characterization of cellular dielectrophoretic (DEP) behaviors, when cells are exposed to an alternating current (AC) electric field of varying frequency, is fundamentally important to many applications using dielectrophoresis. However, to date, that characterization has been performed with monotonically increasing or decreasing frequency, not with successive increases and decreases, even though cells might behave differently with those frequency modulations due to the nonlinear cellular electrodynamic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Combining Eqs. (11) and (12), we are able to describe the iterative method for particle tracing as follows [40]: r n+1 = 2r n r n 1 + 0:5 F n m dt 2 :…”
Section: Particle Tracing Methodsmentioning
confidence: 99%
“…Combining Eqs. (11) and (12), we are able to describe the iterative method for particle tracing as follows [40]: r n+1 = 2r n r n 1 + 0:5 F n m dt 2 :…”
Section: Particle Tracing Methodsmentioning
confidence: 99%
“…Reprinted with permission from [21] copyright (2018) Elsevier B.V. ( E) eDEP + iDEP device used to manipulate MCF‐7 cells. Reproduced from [12] .…”
Section: Hybrid Dep Systemsmentioning
confidence: 99%
“…We note that although there have been efforts to effectively use electrothermal flow for particle/cell manipulation [11], it remains generally viewed as a negative effect for cell trapping. Also, the application of high voltages, independently of the heating effects they produce, may damage the biological sample, decreasing cell viability [12]. Thus, high input‐voltages represent an obstacle toward creating fully integrated, stand‐alone platforms that can be used outside of a laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, efforts have been made on the development of microfluidic platforms and replacing the conventional macrotechniques [10,11]. The microfluidic platforms are suitable for bioscience and biomedical applications, as it requires a small volume of fluid for analysis with advantages of precise transportation control with minimum moving parts and low hydrodynamic dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, trapping force spectroscopy and trap stiffness have been investigated for various DEP trapping. DEP trap stiffness and force spectroscopy were analyzed for particle trapping based on interdigitated electrodes [10,31,32]. It has been reported that the devices with interdigitated electrodes suffer from particle levitation.…”
Section: Introductionmentioning
confidence: 99%